Molecular characterization of the phytopathogen C. theae (Petch) – Causative of birds eye spot infection in Camellia sinensis host through DNA polymorphism and proteome analysis. (April 2022) - Gnanamangai, Balasubramanian Mythili; Philip Robinson, Jayachandran; Ponmurugan, Ponnusamy; AL-mekhlafi, Fahd A.; Farrag, Mohamed A.; Maruthupandy, Muthuchamy; Selvankmuar, Thangaswamy; Sudhakar, Chinnappan
Abstract: The pathogenic fungus Cercospora infecting plants causes high degree symptomatic disease in several important crops including tea ( Camellia sinensis ). Genetic diversity studies on plant pathogens are essential to tackle plant diseases, hence in the proposed study, Cercospora theae isolated from different regions was characterized using the molecular tool like RFLP of the rDNA regions amplified using ITS primers. Protein profiling for all the isolates was also done by optimizing the protein extraction using sodium dodecyl sulphate (SDS), urea and Trichloroacetic acid (TCA) protocols. Genetic relatedness with the identical size of molecular weight among the three C. theae isolates of different regions was studied from the 5.8S rDNA-ITS amplified regions. Digestion of the amplified regions with seven specific endonucleases exposed the same banding pattern among the isolates. The sequence data from the three isolates showed maximum homology with the Genbank sequence of Cercospora spp. (HQ450006, JQ754039, JQ753964, JN942274, JN942272, FJ460222 and EU581822). Further, an optimized protocol for protein profiling of C. theae was determined to extract the majority of the proteins. The results also revealed that the most suitable protocol for studying the proteomics of C. theae was the SDS extraction method. Highlights: First molecular analysis and identification of C. theae causing birds eye spot disease in tea plants. The ITS amplified regions matched with the other  Cercospora   sp  and its taxonomical relations revealed similarity. Proteins of C. theae are well extractable using all the three different protocols. The optimal proteome analysis extraction can be possible with SDS extraction was revealed.